Effect of Probiotics on Growth of Broilers - Suwarno Suwarno; Sajidan Sajidan; Dwi Oetomo; Sri Dwiastuti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of this research are to determine the effect of wheat pollard for broilers, the effect of probiotics on the growth of broiler and interaction between the provision of wheat pollard with probiotics on the growth of broilers. This study used an experimental method with descriptive analysis of quantitative and qualitative with 4x3 experimental design and 6 repetitions. The number of population used is 180 broilers strain CP 202 using a completely randomized design (CRD). Data collection techniques performed since chicken DOC (aged 1 day) until the age of 42 days. The data includes liver length, tibia length and weight. Data analysis using ANOVA two . The most optimal result is obtained by mixing wheat pollard 30% of the diet with probiotics in 10-5. The conclusion from this research are the addition of  probiotics, wheat pollard and interaction of both is effect on the growth of broilers was shown by the results of the statistical analysis Fh> Ft..Keywords: broiler,probiotik,pertumbuhan,phytase